Method and apparatus for displaying data within a three-dimensional information landscape - Steven L. Strasnick; Joel D. Tesler (1996)
A method and apparatus are presented for displaying three-dimensional navigable display space containing an aggregation of graphical objects and an overview of the aggregation of display objects. An altered perspective is provided by compressing the horizontal dimension of the displayed objects so that a user can see a representative overview of the entire aggregation of display objects that have been selected for display together on a display screen. The compressed component is expanded so that the objects appear wider as a navigator approaches the displayed objects. A spotlight shines down on objects responsive to a data query. The spotlight serves as a navigation aid to the navigator so that highlighted items are visible from a distance and can be easily located. The user's view of the display space is altered so that the navigator perceives that he is traveling in a straight line when approaching a display object in a display space in which the horizontal dimension of displayed objects is compressed in accordance with the apparent distance between a displayed object and the navigator.